Estudio del desempeño preclínico y clínico de una amalgama dental comercial (2010)
ABSTRACT: Silver amalgam is a dental material which is used in restorative clinical dentistry for posterior teeth. The purpose of this study was to evaluate the preclinical performance of the Nu Alloy dp® dental amalgam in plastic teeth, and, then to evaluate the clinical performance of the restorative material after eighteen months of being placed in the mouth. Methods: 153 Nu Alloy dp® dental amalgam restorations were made in the preclinical phase and the dentists’ perception was recorded. Subsequently 306 restorations were made in patients in order to evaluate the clinical performance of the restorative material. Results: a good evaluation was reported by the dentists in the preclinical study regarding the following variables: cohesion, carving, burnishing and polishing, with favorable answer percentages between 68% and 86%. Ninety two restorations were examined at the end of the clinical study with following results: excellent evaluation for oclusal wear, cohesive failure of the material, and radiographic evaluation variables; and good evaluation for marginal integrity, surface texture and discoloration variables. Conclusions: good performance results were obtained with Nu Alloy dp® dental amalgam in the preclinical phase which are reflected subsequently in the clinical evaluation results. The results found in the evaluation at eighteen months allowed us to conclude that the clinical performance was excellent. Dental amalgam requires maintenance appointments in order to carry out its polishing every six months and to keep its surface texture and brightness which were obtained in the first appointments.